A vibration-based approach to quantifying the dynamic elastance of the superficial arterial wall. Issue 1 (December 2016) - Wang, Jia-Jung; Liu, Shing-Hong; Su, Hung-Mao; Chang, Steven; Tseng, Wei-Kung
Abstract Background The purpose of this study is to propose a novel method for assessing dynamic elastance of the superficial arterial wall using the sinusoidal minute vibration method. Methods A sinusoidal signal was used to drive a vibrator which induced a displacement of 0.15 mm with a frequency range between 40 and 85 Hz. The vibrator closely contacted with the wall of a superficial radial artery, and caused the arterial wall to shift simultaneously. A force sensor attached to the tip of the vibrator was used to pick up the reactive force exerted by the radial arterial wall. According to the Voigt and Maxwell models, a linear relationship was found between the maximum reactive force and the squared angular frequency of the vibration. The intercept of the linear function represents the arterial wall elastance. In order to validate the feasibility of our method, twenty-nine healthy subjects were recruited and the wall elastances of their radial arteries were measured at room temperature (25 °C), after a 5-min cold stress (4 °C) and a 5-min hot stress (42 °C), respectively. Results After the 5-min cold stimulation, the maximum radial wall elastance significantly increased from 0.441 ± 0.182 × 106  dyne/cm to 0.611 ± 0.251 × 106  dyne/cm (p = 0.001). In the 5-min hot stress, the maximum radial wall elastance significantly decreased to 0.363 ± 0.106 × 106  dyne/cm (p = 0.013). Conclusions The sinusoidal minute vibration method proposed can be employed to obtain the quantitative elastance of a superficial artery under different thermal conditions, and to help assess the severity of arterial stiffness in conduit arteries.